Instrumental (operative) vaginal deliveries: Vacuum extraction compared with forceps delivery at Wad Medani Teaching Hospital, Sudan - Abdalla, Isam Eldien A; Ahmed, Sayed Mohammed; Elhassan, Elhassan Mohmed; Mirghani, Omer Ahmed; Adam, Ishag (Gezira Journal of Health Sciences, 2003)
The risks to the mother and newborn associated with the use of vacuum extractor (V.E.) in comparison with those associated with the use of low delivery forceps (L.D.F.) were studied prospectively. Sixty-nine women were enrolled in to the study, all with single, full term (37 weeks or more) babies, with cephalic presentation, required assisted vaginal deliveries. They were randomized to either vacuum group (38) or forceps (31). Third degree perineal tears, vaginal and cervical lacerations, requirement of blood transfusion were observed less frequently in the group delivered by V.E., the differences were not statistically significant. One baby in the vacuum group developed cephalohaematoma. The vacuum group had a less stay in hospital (more than 48 hours) than the forceps group and the difference is statistically significant. There were no significant differences in the mean birth weight, Apgar scores and the numbers of babies admitted to the intensive care unit. One baby delivered by forceps died shortly after birth. There was no maternal death in either group.